Penetration depth and nonlocal manipulation of quantum spin hall edge states in chiral honeycomb nanoribbons - Yong Xu (Nature Portfolio, 2017)
Abstract We have studied numerically the penetration depth of quantum spin hall edge states in chiral honeycomb nanoribbons based on the Green’s function method. The changing of edge orientation from armchair to zigzag direction decreases the penetration depth drastically. The penetration depth is used to estimate the gap opened for the finite-size effect. Beside this, we also proposed a nonlocal transistor based on the zigzag-like chiral ribbons in which the current is carried at one edge and the manipulation is by the edge magnetization at the other edge. The difficulty that the edge magnetization is unstable in the presence of a ballistic current can be removed by this nonlocal manipulation.